2022
DOI: 10.1039/d1em00447f
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic reduction of 3-nitro-1,2,4-triazol-5-one (NTO) and other munitions constituents by wood-derived biochar through its rechargeable electron storage capacity

Abstract: The environmental fate of 3-nitro-1,2,4-triazol-5-one (NTO) and other insensitive munitions constituents (MCs) is of significant concern due to their high water solubility and mobility relative to legacy MCs. Plant-based biochars...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…Globally, 114–383 million tons (Tg) of BC is produced every year, which represents an integral part of the global carbon cycle. Prior work has shown that BC such as plant-derived biochar and wildfire char possesses sizable and regenerable electron storage capacities (ESCs). The ESC of BC is believed to be composed of redox-facile functional groups such as (hydro)­quinones, which are created through/during pyrolysis . Conceptually, ESC is the sum of the electron-donating capacity (EDC) and electron-accepting capacity (EAC).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, 114–383 million tons (Tg) of BC is produced every year, which represents an integral part of the global carbon cycle. Prior work has shown that BC such as plant-derived biochar and wildfire char possesses sizable and regenerable electron storage capacities (ESCs). The ESC of BC is believed to be composed of redox-facile functional groups such as (hydro)­quinones, which are created through/during pyrolysis . Conceptually, ESC is the sum of the electron-donating capacity (EDC) and electron-accepting capacity (EAC).…”
Section: Introductionmentioning
confidence: 99%
“…7 These energy barriers involved in the "nitro-to-amino" reaction are relatively low, implying that the reaction can easily occur under mild conditions. Although the NTO / ATO reaction is experimentally well documented, 24,30,33,35 this is the rst time that ATO formation on Fe(110) has been observed by AIMD simulations with kinetic information, and we show that this process can be achieved within 4 ps in our simulations.…”
Section: H 2 O Adsorption On Fe(110)mentioning
confidence: 58%
“…Experimentally, NTO anions were veried to be able to complete the "nitro-to-amino" reaction on reducing substances, and the thermodynamic barrier for reducing NTO anions is This journal is © The Royal Society of Chemistry 2023 larger than that for reducing neutral NTO species (cathodic peak potentials, E C = −0.549 and −0.159 eV vs. SHE, respectively). 33,35,69 Therefore, we raise the simulation temperature to 700 K in AIMD to speed up the reaction process of NTO anions on Fe(110), and the corresponding results are shown in Fig. 9(i)-(iv).…”
Section: H 2 O Adsorption On Fe(110)mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations have established that DNAN is subject to cometabolic biotransformation or abiotic reduction in soil and waste streams, which generates an array of metabolites of poorly understood toxicity and increased solubility (Berens et al, 2020; Murillo‐Gelvez et al, 2019; Niedźwiecka et al, 2017; Olivares et al, 2013, 2016; Temple et al, 2018; Xin et al, 2022). For example, the complete reduction of DNAN yields the more reactive 2,4‐diaminoanisole (DAAN), a compound that can rapidly react with partially reduced intermediates, forming a wide array of dimeric metabolites with possible consequences for toxicity (Olivares, Abrell, et al, 2016; Olivares, Sierra‐Alvarez, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%